Post-kidney transplant Whipple’s disease: a case report and literature review - Cunha, Danielle Figueiredo da; Nasser, Natalie Anderson; Vieira, Olga Abrão; Campos, Carlos Frederico Ferreira; Silva, José Carlos Lino da; Matuck, Tereza Azevedo; Carvalho, Deise De Boni Monteiro (Brazilian Journal of Transplantation, 2010)
After more than one hundred years of the description on the Whipple’s disease by George H. Whipple, the diagnosis, pathogenesis and treatment still remain controversial. It is rare disease caused by the Tropheryma whipplei bacterium, which is also found in the environment without causing any damage. Symptoms are nonspecific, such as diarrhea, arthralgia, and weakness; it may present severe cardiac symptoms and in the central nervous system. The most accurate diagnosis is performed by PCR (polymerase chain reaction) and immunohistochemistry, but they are poorly disseminated. Treatment is with intravenous ceftriaxone followed by trimethoprim-sulfamethoxazole for two years. Below, this article describes a case of Whipple’s disease after renal transplantation, which the authors believe to be the second case reported in literature.